Influence of Bacillus apiarius supplementation on the performance of layer chicken - Putu Kompiang; Supriyati .; O Sjofjan (Jurnal Ilmu Ternak dan Veteriner, 2004)
An experiment has been conducted to study the effect of replacing feed additive zinc-bacitracine with probiotic Bacillus apiarius on layer performance. One thousand two hundreds 22-weeks old layers used in this experiment, were divided into three group-treatments and it further divided into 4 subgroups (100 birds/subgroup) as treatment replicates and distributed randomly. Layer in group I were fed basal diet + Growth promotant antibiotic (GPA)-zinc bacitracin, group II were fed basal diet + B. apiarius culture and group III were fed basal diet + commercial probiotic. Feed and water were given ad libitum during the 16 weeks trial. The treatments had no effect (P>0.05) on feed intake. Percentage of hen-day production of group II (88.75 ± 0.88%) was similar to group III (89.58 ± 1.14%), and both were very significantly (P<0.01) higher than group I (77.83 ± 6.21%). Total egg mass production of group II (5.82 ± 0.30 kg/head/16 weeks), was similar to group III (5.64 ± 0.51 kg/head/16 weeks) and both were significantly (P<0.01) higher than group I (4.85 ± 0.45 kg/head/16 weeks). The FCR value of group II (2.48 ± 0.10) was similar to group III (2.43 ± 0.14) and both were very significantly (P<0.01) better than group I (2.86 ± 0.26). The treatments had no effect on egg weight and egg shell thickness. Yolk’s cholesterol content of the group I (4.58 ± 0,56 mg/100 g) was significantly higher than group II (3.72 ± 0.34 mg/100 g) or group III (3.41 ± 0.43 mg/ 100 g). From the present trial it could be concluded that B. apiarius has a potential as probiotic for layer, it even gave better performance and lower cholesterol content of the yolk.   Key words: Layer chickens, probiotic, cholesterol